Evaluation of Acute Supplementation With the Ketone Ester (R)-3-Hydroxybutyl-(R)-3-Hydroxybutyrate (deltaG) in Healthy Volunteers by Cardiac and Skeletal Muscle 31P Magnetic Resonance Spectroscopy - Cameron, Donnie; Soto-Mota, Adrian; Willis, David R.; Ellis, Jane; Procter, Nathan E. K.; Greenwood, Richard; Saunders, Neil; Schulte, Rolf F.; Vassiliou, Vassilios S.; Tyler, Damian J.; Schmid, Albrecht Ingo; Rodgers, Christopher T.; et al. (Frontiers in Physiology, 2022)
In this acute intervention study, we investigated the potential benefit of ketone supplementation in humans by studying cardiac phosphocreatine to adenosine-triphosphate ratios (PCr/ATP) and skeletal muscle PCr recovery using phosphorus magnetic resonance spectroscopy (31P-MRS) before and after ingestion of a ketone ester drink. We recruited 28 healthy individuals: 12 aged 23−70 years for cardiac 31P-MRS, and 16 aged 60−75 years for skeletal muscle 31P-MRS. Baseline and post-intervention resting cardiac and dynamic skeletal muscle 31P-MRS scans were performed in one visit, where 25 g of the ketone monoester, deltaG®, was administered after the baseline scan. Administration was timed so that post-intervention 31P-MRS would take place 30 minutes after ΔG® ingestion. The ΔG® ketone drink was well-tolerated by all participants. In participants who provided blood samples, post-intervention blood glucose, lactate and non-esterified fatty acid concentrations decreased significantly (−28.8%, p≪0.001; −28.2%, p=0.02; and −49.1%, p≪0.001, respectively), while levels of the ketone body D-beta-hydroxybutyrate significantly increased from mean (standard deviation) 0.7 (0.3) to 4.0 (1.1) mmol/L after 30 minutes (p≪0.001). There were no significant changes in cardiac PCr/ATP or skeletal muscle metabolic parameters between baseline and post-intervention. Acute ketone supplementation caused mild ketosis in blood, with drops in glucose, lactate, and free fatty acids; however, such changes were not associated with changes in 31P-MRS measures in the heart or in skeletal muscle. Future work may focus on the effect of longer-term ketone supplementation on tissue energetics in groups with compromised mitochondrial function.